Identifying Development Strategies for Sustainable Rural Tourism Capabilities (Case Studied: rural of Khorramabad town) - Reza Movahedi; fatemeh sepahvand; mehdi rahimian (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
.The community studied, among the experts of the Tourism Organization, professors And students who have been active in the field of tourism was selected Sampling method to Snowball shape was done.Research credibility The survey was conducted from different perspectives.First Available resources available potential tourism potential In the villages of Khorramabad city In various sectors of artistic, natural history, historical and religious sites The case was identified And more Using a semi-structured interview It has been explored the development strategies of this industry Finally, using the ATLAS software As a good quality software, Segregated categories Results showed "Using the traditional potential of villages", "Educational Programs" and "Local People's Participation", "Management and lanning", "Legislation and Policy""Support of Handicraft" and Also pay attention to "advertising" Can contribute to the development of rural tourism in this city.